Culture and identity in Shirley Geok-Lin Lim's Joss and Gold and Jhumpa Lahiri's The Namesake - Rusmanizah binti Ustati (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
This study intends to examine the consequences of colonial and postcolonial experiences in the understanding of an individual's culture and identity. Colonialism changes the political and cultural landscape of a society, and thus it influences the perception of one's cultural identity. This thesis aims to analyse the impact of those experiences towards one's comprehension of self-identity. The framework of postcolonial theory and the theory of hybridity will be applied in the analysis of Shirley Geok-lin Lim's Joss and Gold and Jhumpa Lahiri's The Namesake. These theories will be the premise used in understanding the identity formation of a postcolonial individual.